Enhanced antibacterial activity of TiO2 nanoparticle surface modified with Garcinia zeylanica extract - Senarathna, U.L.N.H.; Fernando, S.S.N.; Gunasekara, T.D.C.P.; Weerasekera, M.M.; Hewageegana, H.G.S.P.; Arachchi, N.D.H.; Siriwardena, H.D.; Jayaweera, P.M. (Chemistry Central Journal, 2017)
Attached

Background: The antibacterial activity of 21 nm TiO2 nanoparticles (NPs) and particles modified with Garcinia zeylanica (G. zeylanica) against Methicillin resistant Staphylococcus aureus was investigated in the presence and absence of light. Results: Surface modification of TiO2 NPs with the adsorption of G. zeylanica extract, causes to shift the absorption edge of TiO2 NPs to higher wavelength. TiO2 NPs, G. zeylanica pericarp extract showed significant bactericidal activity which was further enhanced in contact with the TiO2 modified G. zeylanica extract. Conclusions: The antimicrobial activity was enhanced in the presence of TiO2 NPs modified with G. zeylanica and with longer contact time.
Keywords: Titanium dioxide; Antibacterial; Methicillin-resistant Staphylococcus aureus; Garcinia